PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN PADA MASA PANDEMI COVID-19 - Onih Waronih (LPPM STAI DARUSSALAM LAMPUNG, 2022)
This study aims to analyze the effect of service quality on outpatient satisfaction during the Covid-19 pandemic at the Pangenan Public Health Center UPTD. The method used in this study is a quantitative method. Data collection techniques used are questionnaires and documentation techniques. To determine the number of samples, namely the data on the number of patients for 3 (three) months and using the Slovin formula, it was obtained that 98.94 were rounded up to 100 respondents to be used as samples. This study uses data analysis methods consisting of Validity Test, Reliability Test, Normality Test, Autocorrelation Test, Linear Regression Analysis and Hypothesis T Test. The results of the analysis using simple linear regression through the simple regression equation Y = 7.388 + 0.277 X can be seen that the linear regression equation shows a positive influence of service quality variables on patient satisfaction. The magnitude of the influence of the Service Quality Variable (X) on Patient Satisfaction (Y) is 48.6% while the remaining 51.4% is influenced by other variables not examined in this study. The results of the T-test analysis showed tcount = 9.630 while ttable at freedom (dk) 100-2 = 98 and the significant level = 0.05 was 1.66055. In addition, it is also known that the p-value (sig.t) 0.000 < 0.005 means significant and the tcount 9.630 > t table 1.66055 means significant. Significant here means that Ho is rejected and Ha is accepted.